Guiding Light Selections From the Holy Qur’an: Comments by AbdulHamid A. AbuSulayman (American Journal of Islam and Society, 1991)
TranslationIn the name of Allah, Most Gracious,Most Mercifil.1. Nay, but [Allah is aware of] thosewho keep their bond with Him, andare conscious of Him: and, verily,Allah loves those who are consciousof Him.Al ‘Imran (3:76)2. And spend [freely] in Allah’s cause,and let not your own hands throwyou into destruction; and persevere indoing good: behold, Allah loves thedoers of good.Al Baqarah (2:995)3. And how many a prophet has had tofight [in Allah’s cause], followed bymany Allah-devoted men: and theydid not become faint of heart for allthat they had to suffer in Allah’scause, and neither did they weaken,nor did they abase themselves [beforethe enemy], since Allah loves thosewho are patient in adversity.Al ‘Imran (3:146)4. And it was by Allah’s grace that thou[O Prophet] didst deal gently withthy followers: for if thou hadst beenharsh and hard of heart, they wouldindeed have broken away from thee.Pardon them, then, and pray thatthey be forgiven ...